Peru's National Day and Media - Lloréns, José Antonio (2015)
This article offers a theoretical exploration about the massive display of mediaduring the annual celebration of Peru’s National Day. The exploration is basedon the general assumption that this celebration is a central practice of the Modern State-Nation that maintains its political legitimacy and its institutional continuity. In addition, such practice is part of the resources displayed for cultural conformation of its citizens. In this context, the article proposes a series of considerations regarding the interaction of mass media with the ceremonial State practices.